If (x + 1) and (x

We have,

p (x) = ax3 + x2 – 2x + b

It is given in the question that,

(x + 1) and (x – 1) are the factors of p (x)

p (-1) = p (1)

So, p (-1) = a (-1)3 + (-1)2 – 2 (-1) + b

0 = - a + 1 + 2 + b

0 = - a + 3 + b (i)

Also, p (1) = a (1)3 + (1)2 – 2 (1) + b

0 = a + 1 – 2 + b

0 = a + b – 1 (ii)

As, p (-1) = p (1)

- a + 3 + b = a + b - 1

- 2a = - 4

a = 2

Now, putting the value of a in (ii), we get:

2 + b – 1 = 0

1 + b = 0

b = - 1

Hence, the value of a is 2 and that of b is -1

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses RELATED QUESTIONS :

Factorize:
</p
RS Aggarwal & V Aggarwal - Mathematics

Find the vaRS Aggarwal & V Aggarwal - Mathematics

Factorize:
</p
RS Aggarwal & V Aggarwal - Mathematics

Factorize:
</p
RS Aggarwal & V Aggarwal - Mathematics

If <span lang="ENNCERT Mathematics Exemplar

Show that p – 1 iNCERT Mathematics Exemplar

Factorize:
</p
RS Aggarwal & V Aggarwal - Mathematics

Find the value ofNCERT Mathematics Exemplar

In each of the foRD Sharma - Mathematics